Cardiac involvement in canine babesiosis : review article - R.G. Lobetti (Journal of the South African Veterinary Association, 2005)
Cardiac dysfunction in canine babesiosis has traditionally been regarded as a rare complication, with the majority of lesions reported as incidental findings at post-mortem examination. Recent studies have, however, demonstrated cardiac lesions in canine babesiosis. Cardiac troponins, especially troponin I, are sensitive markers of myocardial injury in canine babesiosis, and the magnitude of elevation of plasma troponin I concentrations appears to be proportional to the severity of the disease. ECG changes in babesiosis are similar to the pattern described for myocarditis and myocardial ischaemia and together with histopathological findings indicate that the heart suffers from the same pathological processes described in other organs in canine babesiosis, namely inflammation and hypoxia. The clinical application of the ECG appears to be limited and thus cardiovascular assessment should be based on functional monitoring rather than an ECG tracing. On cardiac histopathology from dogs that succumbed to babesiosis, haemorrhage, necrosis, inflammation and fibrin microthrombi in the myocardium were documented, all of which would have resulted in ECG changes and elevations in cardiac troponin. Myocardial damage causes left ventricular failure, which will result in hypotension and an expansion of the plasma volume due to homeostatic mechanisms.